Numerical Simulations of White Dwarf Tidal Disruption Events - Humphrey, Sinead (Proceedings of the Wisconsin Space Conference, 2023)
Numerical simulations of white dwarf tidal disruption events are performed using the 3-D moving-mesh hydrody- namic code, MANGA. In order to study the effect of nuclear burning on these events, we add a nuclear burning module to MANGA. Here, we present preliminary results from two simulations of white dwarf tidal disruption events with nuclear burning. We see no nuclear burning for shallow penetration (β = 2); however, we see significant nuclear burning for deep penetration (β = 5). Significant nuclear burning that produces radioactive elements will likely affect the light curve and observability of these events.